Sustainable procurement and role of multiple stakeholders in advancing sustainable performance of the palm oil supply chain - Thangavelu, Indra (2017)
The purpose of this study was to determine if sustainable procurement carried out by the buyers of palm oil would improve the sustainable performance of the palm oil supply chain, and examine the role of the multiple stakeholder initiative, Roundtable on Sustainable Palm Oil (RSPO) in facilitating the buying firms to carry out sustainable procurement. To achieve the purpose, three research questions were formulated to identify the triggers and enablers that will cause the firms to carry out sustainable procurement strategies and practices, evaluate the governing role of RSPO and determine if the strategies and practices of the firms improve the sustainability performance of the chain. To answer these questions, nine latent constructs were developed, underpinned by three broad-based theories; stakeholder theory (stakeholder pressure, sustainability related risk, sustainability oriented people) transaction cost economic (supply chain transparency) and institutional theory (stakeholder integration, stakeholder salience, sustainability performance). A quantitative study by way of webbased survey was undertaken and the sampling frame consisted of RSPO members and non-RSPO members. The sampling method was non-probability purposive sampling method. The findings revealed that stakeholder theory which supported the constructs sustainability related risks and sustainability oriented people positively impacted the procurement strategies but found no support for the construct stakeholder pressure. The supply chain transparency also positively impacted the strategies as predicted by transaction cost economics arising from reduced of opportunistic behavior. The stakeholder theory also supported the positive relationship between sustainable strategies and practices. The role of multi-stakeholder RSPO was tested as a mediating factor on two aspects; stakeholder integration to mediate the firm’s strategy and practice and stakeholder salience to mediate the practice of the firm and its impact on the sustainability performance of the supply chain. And as predicted by the institution theory, the mediating roles of RSPO were affirmed. The institutional theory also supported the positive relationship between sustainable procurement practices and sustainability performances. This study made three theoretical contributions: firstly the dual role of multi-stakeholder; a role in the firms as the firms translate the strategies into implementable practices and a role in the chain as the multi-stakeholder bring firms that share common interest together to improve the sustainability performance of the chain. Secondly, sustainability performance of the chain can only be improved with the adoption of relevant strategies and practices by the firms and thirdly, the categories of governance would also include non-state market driven voluntary initiatives. From a policy perspective, continuing engagement with multi-stakeholders would benefit governments and non-governments as they strive towards improving the sustainability of the palm oil supply chain, a critical commodity which forms the economic backbone of some countries. This study is also important for improving our understating of the role played by the salient multi-stakeholder in the wake of the proliferation of these initiatives.